Revisão taxonômica das espécies brasileiras do grupo rhionaeschna punctata (martin, 1908) (odonata: aeshnidae) - Silva, Larissa de Fátima Ribeiro (2018)
The Rhionaeschna punctata Martin, 1908 species-group was proposed for species of the genus Aeshna, based on male caudal appendage singular shapes which are robust and with apex ventrally curved. Ten species belonging to this group are now recognized, being that five occuring northwestern South America and five are endemic to Brazil (R. punctatasensu estrito): Rhionaeschna punctata, Rhionaeschna decessus (Calvert, 1953); Rhionaeschna eduardoi (Machado, 1985), Rhionaeschna itatiaia (Carvalho& Salgado, 2004) and Rhionaeschna serrana (Carvalho& Salgado, 2004).However, due to the similar morphology and overlapped proposed diagnostic characters, there are problems regarding the validity of these species and their delimitation, which makes it difficult to make an unequivocal association between theavailable namesand the different populations. This present study aimed to perform a taxonomic review of Rhionaeschna punctataspecies group occurring in Brazil, theR. punctatas.s. group, based on the detailed analysis of comparative external morphology of male and female adults. A total of 203specimens from the ABMM, DZRJ, MNRJ and MZUSP collections were examined. From the five available names, three were considered valid and therefore recognized as species (R. decessus, R. eduardoi and R. punctata), with Rhionaeschnaitatiaia being considered junior synonym of Rhionaeschna punctata and Rhionaeschnaserrana junior synonym of Rhionaeschnadecessus. One specie from Rio Grande do Sul and Santa Catarina is proposed, described and illustrated basedon seven males and eight females. For each species of the R. punctatas.s.group, updated synonymy lists, diagnoses, identification keys and distribution maps are presented. Thus, it is concluded that the group Rhionaeschna punctatas.s. is composed by four endemic species of mountainous areas, mainly of the Atlantic Forest, in the Southeastern and Southern regions of Brazil: Rhionaeschna decessus, Rhionaeschna eduardoi, Rhionaeschna punctata andRhionaeschnasp. nov.. Although it has been possible to delimit these species using morphology, they constitute an interesting study